Activity of Javanese Ginger, Turmeric, Garlic, and Pomegranate Flower on LDL-C and Total-C on Dyslipidemia Model Rats - Larissa Larissa; Penny Setyawati Martioso; Diana Krisanti Jasaputra (Global Medical & Health Communication (GMHC), 2021)
High levels of LDL cholesterol are risk factors for coronary heart disease. Different types of medicinal plants have hypolipidemic effects. The study aimed to compare the potential of Javanese ginger ethanol extract, turmeric, garlic, and pomegranate flowers with rosuvastatin on levels of LDL cholesterol (LDL-C) and total cholesterol (total-C) male Wistar rats dyslipidemia models. This experimental laboratory research was conducted in Maranatha Animal Research Laboratory Bandung and was carried out in January–December 2020. The experimental animals were divided into six groups (n=5): the control group, the Javanese ginger group, the turmeric group, the garlic group, the pomegranate flower group, and the comparison control group. The induction given to experimental animals was administering vitamin D3, a high-fat diet, and propylthiouracil for 14 days. The results showed that the administration of 175 mg/kg BW of garlic ethanol extract (−44.85%), pomegranate flowers (−58.74%), and rosuvastatin (−40.00%) reduced LDL-C compared to control (p<0.05). The administration of 175 mg/kg BW of Javanese ginger ethanol extract (−15.16%), turmeric (−14.02%), garlic (−22.80%), pomegranate flower (−65.24%), and rosuvastatin (−18.70%) reduced total-C compared to controls (p<0.05). The conclusion is that garlic and pomegranate flowers lowered LDL-C, while Javanese ginger, turmeric, garlic, and pomegranate flowers reduced total-C. AKTIVITAS TEMULAWAK, KUNYIT, BAWANG PUTIH, DAN BUNGA DELIMA TERHADAP K-LDL DAN K-TOTAL PADA TIKUS MODEL DISLIPIDEMIAKadar kolesterol LDL yang tinggi adalah faktor risiko penyakit jantung koroner. Berbagai jenis tanaman obat memiliki efek hipolipidemik. Penelitian ini bertujuan membandingkan potensi ekstrak etanol temulawak, kunyit, bawang putih, dan bunga delima dengan rosuvastatin pada kadar kolesterol LDL (K-LDL) dan kolesterol total (K-total) tikus Wistar jantan model dislipidemia. Penelitian laboratorium eksperimental ini dilakukan di Laboratorium Penelitian Hewan Maranatha Bandung dan dilakukan pada Januari–Desember 2020. Hewan coba dibagi menjadi enam kelompok (n=5), yaitu kelompok kontrol, kelompok temulawak, kelompok kunyit, kelompok bawang putih, kelompok bunga delima, dan kelompok  pembanding. Induksi yang diberikan kepada hewan coba adalah pemberian vitamin D3, pakan lemak tinggi, dan propyltiouracil selama 14 hari. Hasil penelitian menunjukkan bahwa pemberian 175 mg/kgBB ekstrak etanol bawang putih (−44,85%), bunga delima (−58,74%), dan rosuvastatin (−40,00%) mengurangi K-LDL dibanding dengan kontrol (p<0,05). Pemberian 175 mg/kgBB ekstrak etanol temulawak (−15,16%), kunyit (−14,02%), bawang putih (−22,80%), bunga delima (−65,24%), dan rosuvastatin (−18.70%) mengurangi K-total dibanding dengan kontrol (p<0,05). Kesimpulannya, bunga bawang putih dan delima menurunkan K-LDL, sedangkan temulawak, kunyit, bawang putih, dan bunga delima menurunkan K-total.